Standardization for 13C‐13C clumped isotope analysis by the fluorination method. (11th May 2021) - Taguchi, Koudai; Gilbert, Alexis; Ueno, Yuichiro
Abstract : Rationale: The 13 C‐ 13 C isotopologues of C2 molecules have recently been measured using a fluorination method. The C2 compound is first fluorinated into hexafluoroethane (C2 F6 ), and its 13 C‐isotopologues are subsequently measured using a conventional isotope ratio mass spectrometer. Here, we present an approach for standardizing the fluorination method on an absolute reference scale by using isotopically enriched C2 F6 . Methods: We prepared physical mixtures of 13 C‐ 13 C‐labeled ethanol and natural ethanol. The enriched ethanol samples were measured using the recently developed fluorination method. Based on the difference between the calculated and measured ∆ 13 C 13 C values, we quantified the extent to which isotopologues were scrambled during dehydration, fluorination, and ionization in the ion source. Results: The measured ∆ 13 C 13 C value was approximately 20% lower than that expected from the amount of 13 C‐ 13 C ethanol. The potential scrambling in the ion source was estimated to be 0.5–2%, which is lower than the observed isotopic reordering. Therefore, isotopic reordering may have occurred during either dehydration or fluorination. Conclusions: For typical analysis of natural samples, scrambling in the ion source can only change the ∆ 13 C 13 C value by less than 0.04‰, which is lower than the current analytical precision (±0.07‰). Therefore, the observed isotopic reordering may have occurred during the fluorination of ethene through the scrambling of isotopologues of ethene but not in the ion source of the mass spectrometer or during the dehydration of ethanol, given the small amount of C1 and C3+ molecules. Thus, we obtained the empirical transfer function ∆ 13 C 13 CCSC = λ × ∆ 13 C 13 C with a λ value of 1.25 ± 0.01 for ethanol/ethene and 1.00 for ethane. Using the empirical transfer function, the developed fluorination method can provide actual differences in ∆ values.